ANALISIS IMPLEMENTASI DEMOKRASI PANCASILA DI ERA REFORMASI - Wijayanti, Bernadeta Nefo Eka (PARADIGMA: Jurnal Ilmu Administrasi, 2023)
Pancasila democracy is a consequence of Pancasila as the basis of the state as the philosophichal basis for administering the Indonesian state. The era of Indonesian reformation is the democratization of Indonesia. This article analysis how Pancasila Democracy was implemeted during the reform period after the amandments to the 1945 Constitution. Several things that became the basis for the analysis were the concept of democratization, the concept of Pancasila democracy, democratic practice during the reform period, and several related articles. The result of the analysis show a tendency that implementation of Pancasila Democracy during the reformation was at philosophical level, namely with evidence that the Preamble to the 1945 Constitution which contained Pancasila was not changed, and became the basis for the implementation of Indonesian democracy. The method of deliberation to reach consensus in making decision does not yet take the form of operational guidelines.Keyword: Implementation of Pancasila Democracy; reform period.